LITHOGEOCHEMICAL EXPLORATION FOR DELINEATING PRIMARY GOLD OCCURRENCES IN WEST KAO AREA, NORTH HALMAHERA DISTRICT, NORTH MALUKU PROVINCE - Arifudin Idrus; Fadlin Fadlin (Puslitbang tekMIRA, 2021)
Halmahera Island retains several gold deposits. One of the gold deposits is called as low sulphidation epithermal (LSE) quartz veins which is currently being mined and is situated in the Gosowong goldfield. The veins mostly originated in N-S and NNE-SSW direction. This study is aimed to determine the prospect area in the northern portion of Gosowong goldfield covering the West Kao sub district based on surface mapping and rock/float- and BLEG stream sediment survey. A total of 16 rock/vein float and 120 BLEG samples were analyzed by FA/AAS and CNO2 cyanide leach methods, respectively. The study area is occupied by tuffaceous sandstone, andesite, porphyritic andesite and lava andesite units. In the eastern part, tuffaceous sandstone is suffered from argillic and propylitic alteration, which may be controlled by the NW-SE-trending structures. The gold grade of rock/float samples is up to 0.044 ppm. BLEG data indicates a calculated threshold of 10 ppb for Au and 72 ppb for Ag. The highest Au and Ag contents (anomalies) are identified in the eastern part of the study area. This is spatially (and maybe genetically) related to the argillic-altered tuffaceous sandstone, structures and occurrences of quartz vein floats. To follow up this finding, a detailed exploration is recommended to be conducted within the prospect area.